2015
DOI: 10.1111/medu.12771
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in the use of reflective writing for student assessment: issues of reliability and validity

Abstract: Our findings suggest that to draw meaningful conclusions about reflective capacity as a stable construct in individuals requires 14 writing samples per student, each assessed by four or five raters. This calls into question the feasibility and utility of using reflective writing rigorously as an assessment tool in undergraduate medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 33 publications
(91 reference statements)
1
42
0
4
Order By: Relevance
“…The high scores on self-efficacy in the SEA showed that the students must be receptive to change behaviours according to the teacher's orientation 22,23 and practice what was taught. 39 The results of the REFLECT rubric were similar to the results in other studies (2.60 to 2.71), 40,41 although the inverse correlation of the RS with the self-efficacy calls attention to the possibility that higher academic achievement 42 and improvement of the cognitive process 43 may make students feel less prepared in demonstrating complex behaviours such as professionalism and communication. The selfefficacy in practising a behaviour or skill in professionalism and communication does not necessarily increase the reflection or self-awareness about the situation.…”
Section: Reflection Self-efficacy and Curriculumsupporting
confidence: 84%
“…The high scores on self-efficacy in the SEA showed that the students must be receptive to change behaviours according to the teacher's orientation 22,23 and practice what was taught. 39 The results of the REFLECT rubric were similar to the results in other studies (2.60 to 2.71), 40,41 although the inverse correlation of the RS with the self-efficacy calls attention to the possibility that higher academic achievement 42 and improvement of the cognitive process 43 may make students feel less prepared in demonstrating complex behaviours such as professionalism and communication. The selfefficacy in practising a behaviour or skill in professionalism and communication does not necessarily increase the reflection or self-awareness about the situation.…”
Section: Reflection Self-efficacy and Curriculumsupporting
confidence: 84%
“…Reflection enables students to actively learn from their experiences (Chambers, Brosnan and Hassell, 2011) and assess a range of knowledge, skills and competencies including: professionalism (Stark et al 2006;Hulsman, Harmsen and Fabriek, 2009;Moniz et al 2015), self-care (Saunders et al 2007;Rakel and Hedgecock 2008;Braun et al 2013), empathy, communication, collaboration, clinical reasoning (Moniz et al 2015) and the social determinants of health (van den Heuvel et al 2014). Medical students' ability to reflect is critical for their professional identify formation (Hoffman et al 2016) and ability to work in complex settings (Koole et al 2012).…”
Section: Reflection As a Professional Skillmentioning
confidence: 99%
“…Future studies could incorporate repeat interviews to see whether results are consistent, explore different vignettes to see if similar results will be obtained, and investigate the ideal number of vignettes. 24,25…”
Section: Discussionmentioning
confidence: 99%